Marriage as a Trap in Joyce’s “The Boarding House” - Kandel, Churamoni (AWADHARANA, 2025)
This research article examines and analyzes the institution of ‘marriage’ in James Joyce’s “The Boarding House” as a socially imposed contract, designed to secure economic stability and public respectability rather than personal fulfillment. This study addresses the critical gap in Joyce critiques that often underplays how economic and reputational imperatives shape marital arrangements in the story. Situated within the socio-cultural fabric of early twentieth-century Dublin, marriage emerges here as both a moral expectation and a mechanism of social control. Drawing on feminist and sociological perspectives articulated by Margot Norris and Harry Stone, this analysis foregrounds how Mrs. Mooney, the boarding-house owner, manipulates the romantic involvement between her daughter, Polly, and Mr. Doran to orchestrate a marriage serving her own interests. The findings of the study reveal how Joyce depicts marriage not as a romantic or liberating institution but as a transactional, coercive practice that limits the autonomy of both women and men. By portraying key scenes such as Mrs. Mooney’s calculated confrontation and Mr. Doran’s reluctant acquiescence, this article demonstrates Joyce’s subtle critique of institutionalized marriage. Thus, this study explores the contemporary relevance of Joyce’s critique, especially in ongoing debates about consent, personal freedom, and social expectations in intimate relationships. This study employs a qualitative research design, interpretive approach, and textual analysis method to explore marriage not as a romantic or liberating institution but as a restrictive, coercive trap for women constrained by social and economic pressures in early twentieth- century Dublin.